Synthesis of zeolites from calcareous waste concrete powder - Yasuyuki Kanda; Satori Harada (Results in Materials, 2022)
In this study, zeolites were synthesized from calcareous waste concrete powder (WCP) using a hydrothermal synthesis method. Effective utilization methods of waste concrete are required worldwide for prolonging the final dumping sites’ lifetime and for promoting a society that recycles. Calcareous concrete, which includes many calcium components, has been widely used. The WCP includes mainly calcite (at 66.9%) and quartz. First, we applied hydrothermal synthesis to raw WCP. However, X-ray diffraction analysis (XRD) revealed no zeolite synthesis. Next, we used the same approach on WCP-HCl (WCP with the calcium component removed by HCl treatment). For WCP-HCl, the synthesis of analcime-type zeolites was confirmed based on XRD and simple absorption tests, in which the WCP-HCl color changed from gray to blue upon its absorption of methylene blue. Finally, to determine the analcime synthesis requirements, we experimentally varied the synthesis. Analcime synthesis was observed at temperatures above 433 K after at least 12 h of heating and for NaOH solution concentrations above 2 mol/L.